Women of the Street : How the Criminal Justice-Social Services Alliance Fails Women in Prostitution. - Dewey, Susan (NYU Press, 2017)
This is a work about people who make their living by engaging in street-based sex trading and criminal justice and social services efforts to curtail it through the work of police officers, public defenders, judges, probation officers, or court-mandated therapeutic treatment providers. Coauthored by an anthropologist and a legal scholar, the text explores these interactions and the cultural context in which they take place by drawing upon six years of ethnographic research with hundreds of women involved in street-based prostitution and illicit drug use, as well as dozens of the criminal justice and social services professionals who regularly interact with them.